Proceedings of the International Conference on Intelligent Systems and Digital Transformation (ICISD 2025) - Golda Dilip; P. Durgadevi; K. Akila; S. Sridevi; Raj Ramachandran (Atlantis Press International BV, 2025)
This open access volume presents the Proceedings of the International Conference on Intelligent Systems and Digital Transformation (ICISD 2025).